2020
DOI: 10.1017/s1355617720000314
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Greek ACE-III, M-ACE, ACE-R, MMSE, and ECAS in the Assessment and Identification of Alzheimer’s Disease

Abstract: Objective: This study aimed to adapt the Addenbrooke’s Cognitive Examination-III (ACE-III) and Mini-Addenbrooke’s Cognitive Examination (M-ACE) into Greek and then to examine the convergent validity against their predecessors Addenbrooke’s Cognitive Examination-Revised (ACE-R) and Mini-Mental State Examination (MMSE) in a Greek population. Moreover, a primary aim was to appraise the utility of each screen by conducting a comparison of the psychometric properties of ACE-III, M-ACE, ACE-R, MMSE, and the Edi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Furthermore, the AD group from this previous study 6 were older than the current study (mean age of 67.19 vs. 61.18 years old respectively), and it is possible that early onset AD (<65 years of age) may have a slightly different cognitive profile from late onset. 45,46 Nevertheless, a further study which compared the Greek version of the ECAS with the ACE-III 22 found similar results to those reported here; in which both composite scores were sensitive to AD, with the posterior composite score being the most sensitive measure. Strengths of this study were its thorough investigation of the clinical validity of the ECAS with these dementia groups and the inclusion of well characterised patients (diagnoses supported by imaging, CSF, and/or genetic analysis).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the AD group from this previous study 6 were older than the current study (mean age of 67.19 vs. 61.18 years old respectively), and it is possible that early onset AD (<65 years of age) may have a slightly different cognitive profile from late onset. 45,46 Nevertheless, a further study which compared the Greek version of the ECAS with the ACE-III 22 found similar results to those reported here; in which both composite scores were sensitive to AD, with the posterior composite score being the most sensitive measure. Strengths of this study were its thorough investigation of the clinical validity of the ECAS with these dementia groups and the inclusion of well characterised patients (diagnoses supported by imaging, CSF, and/or genetic analysis).…”
Section: Discussionsupporting
confidence: 85%
“…In the early stages of both bvFTD and AD, deterioration typically follows a region-specific pattern with frontal lobe dysfunction beginning in the orbitofrontal cortex in bvFTD 19 ; and medial temporal and occipitoparietal regions in AD. 20,21 Recent studies have revealed that the ECAS composite score, compromising memory and visuospatial performance, was as sensitive to AD as the ACE-III 22 and was effective at differentiating ALS from AD in a Greek population. 6 This study aimed to validate the ECAS and further determine its clinical utility in detecting the cognitive and behavioural impairments in bvFTD in comparison with AD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although our sample size was not large, it was comparable to other validation studies of the mini-ACE in dementia such as the Brazilian version (dementia = 23 and controls = 25) [20], the Thai version (dementia = 48 and controls = 60) [22] and the Greek version (dementia = 40 and controls = 38) [23]. In addition, our sample size was adequate to provide high sensitivity (92%), high specificity (95%), and high accuracy (94%) for the cutoff score calculated that was comparable to other studies.…”
Section: Discussionsupporting
confidence: 62%
“…Our optimal cutoff point was 18 out of 30, which was lower than the upper cutoff score provided by the English language version of the m-ACE (which was 25) but comparable with the lower cutoff score (which was 21) [4]. Other language versions’ cutoff scores ranged from 16 to 23 out of 30, so our cutoff score of 18 can be considered midrange: 16/30 for the Spanish version (86.7% sensitivity and 87% specificity) [19]; 20/30 for the Brazilian version (95.7% sensitivity and 90.2% specificity) [20]; 21–22/30 for the Chinese version (96% sensitivity and 87% specificity) [21]; 16–17/30 for the Thai version (95.8% sensitivity and 85% specificity) [22]; and 23/30 for the Greek version (97.4% sensitivity and 94.7% specificity) [23].…”
Section: Discussionmentioning
confidence: 99%
“…The M-ACE is also proven to be more sensitive and have less ceiling effect than MMSE. Studies from Japan and Greece showed that their linguistic versions of M-ACE were superior to MoCA in detecting MCI and dementia [ 59 , 68 ], but studies using the English or Chinese versions of M-ACE did not reach the same conclusion [ 39 , 69 ]. In addition, the Chinese version of M-ACE also shows comparable accuracy to the Chinese version of ACE-III (AUC 0.892 vs. 0.901) [ 39 ].…”
Section: Comparison Of Chinese Versions Of Ace With Other Screening T...mentioning
confidence: 99%